Nepal’s military diplomacy: Retrospect and prospect - Ghimire, Pragya (Unity Journal, 2020)
Military diplomacy has been an important security and foreign policy tool for many centuries. However, in the age of globalization, its importance has grown more rapidly than ever because of the recognition that country’s survival and development also depend on a peaceful and stable national and regional environment. Some of the significant practices in the past reflect that various tools of military diplomacy could be implemented to strengthen country’s overall diplomacy, including bilateral and multi-lateral contacts of military and civilian defence officials of foreign countries; preparing bilateral/multilateral security and defence agreements; exchanging experience with foreign military and civilian defence officials; providing military assistance and support to other countries, such as aid, materials and equipment when there is need and request during the disaster or humanitarian crises. However, these tools of strengthening military diplomacy will not be as effective as expected if there is no effective civil-military relations and synergies between a country’s national security and foreign policy. Moreover, it will require strong expertise and good command of civilian diplomats on security issues and military diplomats on foreign policy issues. To strengthen its military diplomacy to contribute to Nepal’s overall diplomacy and foreign policy, it will require more military attaché in Nepal foreign diplomatic missions of vital security and development interest. Moreover, Nepal should continue building synergies between its national security, foreign and development policies as well as strengthening military diplomacy both at bilateral and regional levels.